ANALYSIS OF THE GAZE BEHAVIOUR OF THE WORKER ON THE CARBURETOR ASSEMBLY TASK - Susanto, Novie (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2015)
This study presents analysis of the area of interest (AOI) and the gaze behavior of human during assembly task. This study aims at investigating the human behavior in detail using an eyeâ€tracking system during assembly task using LEGO brick and an actual manufactured product, a carburetor. An analysis using heat map data based on the recorded videos from the eye-tracking system is taken into account to examine and investigate the gaze behavior of human. The results of this study show that the carburetor assembly requires more attention than the product made from LEGO bricks. About 50% of the participants experience the necessity to visually inspect the interim state of the work object during the simulation of the assembly sequence on the screen. They also show the tendency to want to be more certain about part fitting in the actual work object. Â